2021
DOI: 10.1016/j.heliyon.2021.e06828
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the spatial distribution of evapotranspiration within the Pra River Basin of Ghana

Abstract: It is important in water resource planning to accurately estimate the spatial distribution of evapotranspiration (ET) as an input parameter for hydrological studies. Although, conventional pan evaporation, lysimetric and eddy covariance techniques have been used, they only estimate point values. Hence, this study aimed at estimating the spatial distribution of ET within the Pra River Basin (a forest ecological zone) of Ghana, using cloud-free Landsat 8 (OLI/TIRS) satellite images employing the SEBAL methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In 2017, the same pattern occurred in the distribution of ET0 by this difference that data is reduced. Nsiah et al (2021) showed a variation of ET was higher in the western, central, and eastern parts of the Pra River Basin of Ghana, but it was lower in the northern and southern parts of the basin where there are many settlements and forests. Chang et al (2023) showed that in Tibetan Plateau's from the southeast to the northwest the multiyear mean annual ET decreased.…”
Section: Et0 Zonationmentioning
confidence: 91%
See 1 more Smart Citation
“…In 2017, the same pattern occurred in the distribution of ET0 by this difference that data is reduced. Nsiah et al (2021) showed a variation of ET was higher in the western, central, and eastern parts of the Pra River Basin of Ghana, but it was lower in the northern and southern parts of the basin where there are many settlements and forests. Chang et al (2023) showed that in Tibetan Plateau's from the southeast to the northwest the multiyear mean annual ET decreased.…”
Section: Et0 Zonationmentioning
confidence: 91%
“…The results showed a decrease in the climate balance due to a decrease in precipitation and an increase in ET0 during the study period. Nsiah et al (2021) assessed the spatial changes of evapotranspiration in the Pra River Basin of Ghana. The spatial variation of ET was higher in the western, central, and eastern parts of the basin, but it was lower in the northern part and parts of the southern part of the basin where there are many settlements and forests.…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing can also be used for crop classification, crop monitoring during the growth season, and crop production assessment. In this regard, the remote sensing technology with global positioning systems (GPS) and geographical information systems (GIS) can be used to improve the efficiency in agricultural activities such as farmland extent estimation, crop growth stages monitoring, soil moisture and fertility evaluation, crop stress detection, diseases and pest disperse, drought and flood situations monitoring, and weather forecasting [7,64,[79][80][81].…”
Section: Current Status Of the Et Estimation In Agricultural Water Ma...mentioning
confidence: 99%
“…The water budget allows for the water circulation rate and changes in water retention in all sections of the atmosphere, land surface, and sub-surface (Chandra et al, 2022). Through evaporation, water from the Earth enters the atmosphere and is lost to it as precipitation, primarily rain or snow (Nsiah et al, 2021). Water that seeps through the ground can stay in the unsaturated zone, where it will probably evaporate or transpire from plants and return to the atmosphere.…”
Section: 0: Introductionmentioning
confidence: 99%